Dual Carrier PWM Inverter-Fed Nine-Phase AC Motors - Anwar Muqorobin; Pekik Argo Dahono; Estiko Rijanto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
In many applications such as electric vehicles, dual mode operation is needed, i.e pulsewidth modulation (PWM) mode for low speed region and squarewave mode for high speed region. The latest research has shown that symmetrical ninephase motor could provide optimal characteristics under dual mode operation, i.e. minimum nverter input and rotor current ripples. By using analytical calculation, in this paper the authors show that asymmetrical nine-phase motor can also provide the optimal characteristics under dual mode operation by simply using dual carrier PWM. This finding is supported by experimental results.